A method for preparing a strong and tough amorphous CuZr-crystalline Cr gradient multilayer film
By inserting a crystalline Cr layer with a gradient distribution of thickness into the matrix of the amorphous CuZr layer, an amorphous-crystalline gradient multilayer film is formed, which solves the problem of brittle fracture of amorphous alloys at low temperatures and significantly improves the Its strength, toughness and mechanical properties.
Patent Information
- Application Number
- CN202410562168.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-08
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-05-08
AI Technical Summary
Existing amorphous alloys are prone to brittle fracture at low temperatures, lacking macroscopic plastic deformation and strain strengthening stages, limiting their application scope.
Magnetron sputtering technology is used to insert a crystalline Cr layer with a gradient distribution of thickness into the matrix of the amorphous CuZr layer to form an amorphous-crystalline gradient multilayer film.
By introducing a gradient crystalline Cr layer, the toughness of amorphous CuZr is significantly improved and its mechanical properties at low temperatures are enhanced, including nanoindentation hardness and modulus, as well as the yield strength and elongation of micropillars.
Smart Images

Figure CN118422126B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of multilayer film magnetron sputtering manufacturing, and in particular to a method for preparing a strong and tough amorphous CuZr-crystalline Cr gradient multilayer film. Background Art
[0002] Although amorphous alloys exhibit a series of excellent mechanical properties, such as high strength, low elastic modulus, high elastic deformation capacity, and superplasticity at high temperatures, there are some unsatisfactory problems at low temperatures. Most amorphous materials tend to undergo sudden brittle fracture at low temperatures, with almost no macroscopic plastic deformation and strain hardening stages. This feature greatly reduces the reliability of amorphous materials and severely limits their scope of application. Therefore, how to enhance the strength and toughness of amorphous alloys while retaining the inherent advantages of amorphous alloys has always been an important research direction in this field. In addition to regulating the composition of amorphous alloys, the more commonly used method is to use an amorphous composite method. This method adds second phase materials, such as nanoparticles, dendrite phases, fibers, etc., to amorphous alloys to improve their strength and toughness by preparing amorphous composite materials.
[0003] Among them, multilayer film is a typical artificial structural material. Its structure can be precisely controlled by methods such as vacuum coating, and then its mechanical properties can be precisely controlled with good repeatability. Therefore, multilayer film provides a convenient means for us to understand the mechanical properties of layered structural materials. In recent years, multilayer film materials have attracted widespread attention and become one of the hot spots in the research of thin film materials. In addition, for amorphous films, a composite method that is easy to implement and precisely control is to use amorphous as the matrix and insert other material layers to form a multilayer film structure. How to regulate the composition and structure of the multilayer film to obtain a multilayer film with good toughness and excellent comprehensive performance is the focus of research by technicians in this field at this stage. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a strong and tough amorphous CuZr-crystalline Cr gradient multilayer film to solve the problems existing in the above-mentioned prior art.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention: a method for introducing a gradient crystalline layer to enhance the toughness of an amorphous film, taking an amorphous film as a matrix, inserting a multilayer crystalline layer with a gradient thickness distribution into the amorphous film, and obtaining an amorphous-crystalline gradient multilayer film in which amorphous layers and crystalline layers are alternately superimposed.
[0007] Furthermore, the amorphous layer is a CuZr layer, and the crystalline layer is a Cr layer.
[0008] The second technical solution of the present invention: a strong and tough amorphous CuZr-crystalline Cr gradient multilayer film, which is obtained by alternatingly superimposing amorphous CuZr layers and crystalline Cr layers, wherein the thickness of the amorphous CuZr layers is consistent, and the thickness of the crystalline Cr layer increases gradiently from bottom to top; the bottom layer of the strong and tough amorphous CuZr-crystalline Cr gradient multilayer film is the amorphous CuZr layer.
[0009] As a further preferred embodiment of the present invention, the element composition of the amorphous CuZr layer is Cu 50 Zr 50 ; The single layer thickness of the amorphous CuZr layer is 210±5nm; The amorphous CuZr layer has a total of 9 layers.
[0010] As a further preferred embodiment of the present invention, the crystalline Cr layer has 8 layers in total, and the thickness of each layer from bottom to top is 22±5, 44±5, 70±5, 93±5, 124±5, 144±5, 167±5, and 190±5 nm.
[0011] As a further preferred embodiment of the present invention, the amorphous CuZr layer and the crystalline Cr layer are alternately stacked on the substrate, and the first layer directly in contact with the substrate is the amorphous CuZr layer. That is, the tough amorphous CuZr-crystalline Cr gradient multilayer film is equivalent to inserting 8 layers of crystalline Cr layers with gradient thickness distribution into the amorphous CuZr film matrix.
[0012] The third technical solution of the present invention is as follows: the method for preparing the tough amorphous CuZr-crystalline Cr gradient multilayer film comprises the following steps:
[0013] By utilizing magnetron sputtering technology and taking CuZr target material and Cr target material as sputtering raw materials, amorphous CuZr layers and crystalline Cr layers are alternately sputtered and deposited on a substrate to obtain the tough amorphous CuZr-crystalline Cr gradient multilayer film.
[0014] As a further preferred embodiment of the present invention, the substrate is <111> The first layer deposited by sputtering on the substrate is an amorphous CuZr layer.
[0015] As a further preferred embodiment of the present invention, the sputtering power of the CuZr target is 60W, and the sputtering power of the Cr target is 30W.
[0016] As a further preferred embodiment of the present invention, the CuZr target material is specifically Cu 50 Zr 50 Target material: The CuZr target material and the Cr target material are prepared by a powder metallurgy method.
[0017] As a further preference of the present invention, the sputtering time of each amorphous CuZr layer is 16 min, and the sputtering time of each crystalline Cr layer from bottom to top is 2, 4, 6, 8, 10, 12, 14, and 16 min, respectively.
[0018] The sputtering time is fixed, and the thickness of the amorphous CuZr layer and the thickness of each crystalline Cr layer are limited to a range value because the working gas pressure is unstable during the sputtering process, resulting in an unstable sputtering rate. Therefore, when repeatedly preparing multilayer films, even if the sputtering time is the same twice, the final thickness will fluctuate slightly.
[0019] As a further preferred embodiment of the present invention, the argon working pressure for the alternate sputtering deposition of the amorphous CuZr layer and the crystalline Cr layer is 1Pa.
[0020] As a further preferred embodiment of the present invention, before the alternating sputtering deposition of the amorphous CuZr layer and the crystalline Cr layer, the process further includes cleaning the CuZr target, the Cr target and the substrate.
[0021] As a further preferred embodiment of the present invention, the cleaning operation of the CuZr target and the Cr target is as follows: grinding the surface oxide of the target with 80-mesh and 120-mesh sandpapers in turn, then cleaning the surface with anhydrous ethanol, and finally drying with a hair dryer.
[0022] As a further preferred embodiment of the present invention, the cleaning operation performed on the substrate is specifically: ultrasonically cleaning the substrate for two minutes under acetone reagent, and finally drying it with a hair dryer.
[0023] As a further preferred embodiment of the present invention, before the alternate sputtering deposition of the amorphous CuZr layer and the crystalline Cr layer, the CuZr target material and the Cr target material are pre-sputtered.
[0024] As a further preferred embodiment of the present invention, the pre-sputtering treatment time is 10 minutes.
[0025] As a further preferred embodiment of the present invention, the method for preparing the tough amorphous CuZr-crystalline Cr gradient multilayer film specifically comprises the following steps:
[0026] S1. Preparation of target materials: CuZr target materials and Cr target materials are prepared by powder metallurgy method;
[0027] S2. Cleaning of the target and substrate: Grind the surface oxide of the target with 80-mesh and 120-mesh sandpapers in turn, then clean the surface with anhydrous ethanol, and finally blow dry with a hair dryer; ultrasonically clean the substrate in acetone reagent for two minutes, and finally blow dry with a hair dryer;
[0028] S3. Preparation of amorphous CuZr-crystalline Cr gradient multilayer film:
[0029] S3.1. Place the CuZr target, Cr target and substrate into the chamber of the magnetron sputtering instrument;
[0030] S3.2, first use mechanical pump and molecular pump to pump the vacuum degree in the chamber to 4×10 -4 Pa, then open the argon valve and adjust the molecular pump valve to make the working gas pressure in the chamber 3Pa;
[0031] S3.3. Set the sputtering power of the CuZr target and the Cr target, turn on the DC power supply, adjust the molecular pump valve so that the working gas pressure in the chamber is 1 Pa, pre-sputter both targets for 10 minutes, and then perform alternating sputtering deposition of amorphous CuZr layer and crystalline Cr layer.
[0032] The present invention discloses the following technical effects:
[0033] The present invention introduces a crystalline Cr layer with a gradient thickness distribution into the amorphous CuZr by alternately superimposing an amorphous CuZr layer and a crystalline Cr layer, thereby obtaining a strong and tough amorphous CuZr-crystalline Cr gradient multilayer film, wherein the amorphous CuZr layer and the crystalline Cr layer have good bonding force, and the obtained strong and tough amorphous CuZr-crystalline Cr gradient multilayer film has good bonding between the layers, and no defects such as cracks are generated. The introduction of the gradient crystalline Cr layer significantly improves the toughness of the amorphous CuZr, mainly because the thickness of the gradient Cr layer presents a gradient change, resulting in a complex stress field formed at the interface between the Cr crystal layer and the CuZr amorphous layer in the entire film, thereby further limiting the expansion of the shear band in the amorphous layer, thereby improving its strong plastic deformation ability.
[0034] The amorphous CuZr-crystalline Cr gradient multilayer film prepared by the present invention has good mechanical properties: the hardness and modulus of nanoindentation are 10.6 GPa and 176 GPa respectively; the yield strength of microcolumns with a diameter of 1 μm and a height of 2 μm cut from the multilayer film after compression is 3.2 GPa, and the elongation reaches 50% without failure; scanning electron microscopy shows that the deformed microcolumns are bucket-shaped and no obvious cracks appear. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 This is a longitudinal cross-sectional morphology of the amorphous CuZr-crystalline Cr gradient multilayer film obtained in Example 1;
[0037] Figure 2 Nanoindentation test results of the films of Example 1, Comparative Example 1 and Comparative Examples 3-4;
[0038] Figure 3 This is a morphology image of the micro-pillars of the amorphous CuZr-crystalline Cr gradient multilayer film obtained in Example 1 before deformation;
[0039] Figure 4 This is a morphology image of the micro-pillars of the amorphous CuZr-crystalline Cr gradient multilayer film obtained in Example 1 after deformation;
[0040] Figure 5 1 is the compressive stress-strain curve of the microcolumns of the films of Example 1, Comparative Example 1 and Comparative Examples 3-4;
[0041] Figure 6 This is a longitudinal cross-sectional morphology of the CuZr film obtained in Comparative Example 1;
[0042] Figure 7 This is a morphology of the micro-pillars of the CuZr film obtained in Comparative Example 1 after deformation;
[0043] Figure 8 This is a longitudinal cross-sectional morphology of the Cr film obtained in Comparative Example 2;
[0044] Fig. 9 This is a longitudinal cross-sectional morphology of the amorphous CuZr-crystalline Cr multilayer film of equal thickness obtained in Comparative Example 3;
[0045] Fig.10 The morphology of the micro-pillars of the amorphous CuZr-crystalline Cr multilayer film of equal thickness obtained in Comparative Example 3 before deformation;
[0046] Fig.11 The morphology of the micro-pillars of the amorphous CuZr-crystalline Cr multilayer film of equal thickness obtained in Comparative Example 3 after deformation;
[0047] Fig.12 This is a longitudinal cross-sectional morphology of the amorphous CuZr-crystalline Al gradient multilayer film obtained in Comparative Example 4;
[0048] Fig.13 This is the morphology of the micro-columns of the amorphous CuZr-crystalline Al gradient multilayer film obtained in Comparative Example 4 after deformation. DETAILED DESCRIPTION
[0049] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0050] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0051] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0052] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0053] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0054] In the following embodiments, there is no specific limitation on the specific operation method of preparing the target material by powder metallurgy, and the target material that can be used for sputtering can be obtained by conventional methods in the art.
[0055] Example 1
[0056] A preparation method of an amorphous CuZr-crystalline Cr gradient multilayer film, comprising the following steps:
[0057] Target preparation: According to Cu 50 Zr 50 The raw materials are proportioned according to the molar ratio of elements in the (CuZr) chemical composition, and then a CuZr target with a diameter of 50 mm and a thickness of 5 mm is prepared by a powder metallurgy method. Cr powder is used as the raw material, and a Cr target with a diameter of 50 mm and a thickness of 5 mm is prepared by a powder metallurgy method.
[0058] Cleaning of the target and substrate: Before sputtering, the surface oxides of the CuZr target and the Cr target were polished with 80-mesh and 120-mesh sandpapers respectively, and then the surfaces were cleaned with anhydrous ethanol, and finally the two targets were dried with a hair dryer; the substrate was selected from 10×10×0.5mm 3 Size <111> For single crystal silicon wafers with different crystal orientations, the silicon wafer substrate is ultrasonically cleaned in acetone reagent for two minutes and finally dried with a hair dryer.
[0059] Preparation of amorphous CuZr-crystalline Cr gradient multilayer film: CuZr target, Cr target and silicon wafer substrate are placed in the chamber of the magnetron sputtering instrument (two targets are placed on two target heads in the chamber respectively, and the silicon wafer substrate is glued to two substrates with high-temperature tape, and the two substrates are perpendicular to the two targets respectively), and the chamber is closed; the mechanical pump is started first, and then the mechanical pump valve is opened, and the vacuum in the chamber is pumped until the vacuum degree in the chamber reaches below 5Pa, and then the mechanical pump valve is closed; then the molecular pump is started, and then the molecular pump valve is opened, and the vacuum degree in the chamber is pumped until the vacuum degree in the chamber reaches 4×10 -4 Pa, then open the argon valve, and then adjust the molecular pump valve to make the working gas pressure in the chamber 3Pa; first set the DC sputtering power of CuZr and Cr targets to 60W and 30W respectively, then turn on the DC power switch to start ignition, and observe whether it is ignited through the observation window. After ignition is successful, adjust the molecular pump valve to make the working gas pressure in the chamber 1Pa, both targets are pre-sputtered for 10min and then the surface of the lower target is cleaned. Finally, when sputtering alternately on the substrate, the amorphous CuZr layer is sputtered first. The sputtering time of each layer of the amorphous CuZr layer is 16min to make the thickness reach about 210nm, and a total of 9 layers are deposited; the sputtering time of each layer of the crystalline Cr layer from bottom to top is 2, 4, 6, 8, 10, 12, 14, and 16min, and a total of 8 layers are deposited, with thicknesses of 22, 44, 70, 93, 124, 144, 167, and 190nm respectively; finally, turn off the DC power switch, cool for 30min, and then open the chamber to take out the sample.
[0060] The longitudinal cross-sectional morphology (SEM image) of the amorphous CuZr-crystalline Cr gradient multilayer film obtained in this embodiment is as follows: Figure 1 As shown by Figure 1 It can be seen that the longitudinal section of the sample presents an obvious multilayer film structure, and the thickness of the Cr layer increases gradually from bottom to top. From the SEM image, it can also be seen that there are no obvious cracks or holes at the interface between the CuZr layer and the Cr layer, indicating that the two are well combined. The multilayer film was subjected to nanoindentation testing, and the results are as follows: Figure 2 As shown in FIG. 1 , the hardness and modulus of the multilayer film by nanoindentation are 10.6 GPa and 176 GPa, respectively. Then, a microcolumn with a diameter of 1 μm and a height of 2 μm was cut from the region of the multilayer film that was not subjected to the nanoindentation test (cut from the top layer downwards) by a focused ion beam. The morphology (SEM image) is shown in FIG. Figure 3 The microcolumn is then compressed by nano-indentation technology. Since the multilayer film has good plasticity, the compression is stopped when the strain reaches about 50% but it does not fail. The morphology after compression (SEM image) is shown as follows Figure 4 As shown by Figure 4 It can be seen that the microcolumn is in a bucket shape after compression and no cracks are generated. The stress-strain curve of the microcolumn compression is shown in Figure 5 As shown, it can be concluded that the yield strength of the multilayer film reaches 3.2 GPa when the strain reaches 50%.
[0061] Comparative Example 1
[0062] A preparation method of an amorphous CuZr film comprises the following steps:
[0063] Target preparation: According to Cu 50 Zr 50 The raw materials are proportioned according to the molar ratio of elements in the (CuZr) chemical composition, and then a CuZr target with a diameter of 50 mm and a thickness of 5 mm is prepared by a powder metallurgy method.
[0064] Cleaning of the target and substrate: Before sputtering, use 80-mesh and 120-mesh sandpaper to grind the surface oxide of the CuZr target, then clean the surface with anhydrous ethanol, and finally dry the target with a hair dryer; the substrate is 10×10×0.5mm 3 Size <111> For single crystal silicon wafers with different crystal orientations, the silicon wafer substrate is ultrasonically cleaned in acetone reagent for two minutes and finally dried with a hair dryer.
[0065] Preparation of CuZr thin film: The CuZr target and silicon wafer substrate were placed in the chamber of the magnetron sputtering instrument, and then the chamber was closed; the mechanical pump was started first, and then the valve of the mechanical pump was opened, and the vacuum in the chamber was pumped until the vacuum degree in the chamber reached below 5 Pa, and then the valve of the mechanical pump was closed; the molecular pump was started, and then the valve of the molecular pump was opened, and the vacuum degree in the chamber was pumped until the vacuum degree in the chamber reached 4×10 -4 Pa, then open the argon valve, and then adjust the molecular pump valve to make the working gas pressure in the chamber 3Pa; first set the DC sputtering power to 60W, then turn on the DC power switch to start ignition, and observe whether it is ignited through the observation window. After successful ignition, adjust the molecular pump valve to make the working gas pressure in the chamber 1Pa, pre-sputter for 10 minutes, then clean the target surface, and then sputter for 3.5 hours to deposit a film of a certain thickness; finally, turn off the DC power switch, cool for 30 minutes, and then open the chamber to take out the sample.
[0066] The longitudinal cross-sectional morphology of the amorphous CuZr film obtained in this comparative example is shown in FIG. Figure 6 As shown by Figure 6 It can be seen that the longitudinal section of the sample presents an obvious fibrous structure, and the thickness of the film is 2.4 μm. The film was subjected to nanoindentation testing, and the results are as follows Figure 2 As shown in Figure 1, the hardness and modulus of the film by nanoindentation are 7.8 GPa and 130 GPa respectively. Then, a microcolumn with a diameter of 1 μm and a height of 2 μm was cut from the region of the film that was not subjected to the nanoindentation test (cut from the top layer downwards) by a focused ion beam, and then the microcolumn was compressed by nanoindentation technology. The stress-strain curve of the microcolumn compression is shown in Figure 1. Figure 5 As shown by Figure 5 It can be seen that due to the poor plasticity of the film, catastrophic failure occurs when the strain reaches 15%. The yield strength during compression is 1.7 GPa. The morphology after compression (SEM image) is shown in Figure 7 As shown by Figure 7 It can be seen that the deformed micropillars show obvious shear band deformation, which is consistent with the deformation characteristics of amorphous alloys.
[0067] Comparative Example 2
[0068] A preparation method of a crystalline Cr film comprises the following steps:
[0069] Preparation of target material: Using Cr powder as raw material, a Cr target with a diameter and thickness of 50 mm and 5 mm respectively was prepared by powder metallurgy method.
[0070] Cleaning of the target and substrate: Before sputtering, use 80-mesh and 120-mesh sandpaper to grind the surface oxide of the Cr target, then clean the surface with anhydrous ethanol, and finally dry the target with a hair dryer; the substrate is 10×10×0.5mm 3 Size <111> For single crystal silicon wafers with different crystal orientations, the silicon wafer substrate is ultrasonically cleaned in acetone reagent for two minutes and finally dried with a hair dryer.
[0071] Preparation of Cr film: Place the Cr target and silicon wafer substrate into the chamber of the magnetron sputtering instrument and close the chamber; start the mechanical pump first, then open the valve of the mechanical pump, and continue pumping until the vacuum degree in the chamber reaches below 5 Pa, then close the valve of the mechanical pump; then start the molecular pump, then open the valve of the molecular pump, and continue pumping until the vacuum degree in the chamber reaches 4×10 -4 Pa, then open the argon valve, and then adjust the molecular pump valve to make the working gas pressure in the chamber 3Pa; first set the DC sputtering power to 30W, then turn on the DC power switch to start ignition, and then observe whether it is ignited through the observation window. After successful ignition, adjust the molecular pump valve to make the working gas pressure in the chamber 1Pa, pre-sputter for 10 minutes, then clean the target surface, and then sputter for 2 hours to deposit a film of a certain thickness; finally, turn off the DC power switch, cool for 30 minutes, and then open the chamber to take out the sample.
[0072] The longitudinal cross-sectional morphology of the crystalline Cr film obtained in this comparative example is shown in FIG. Figure 8 As shown by Figure 8It can be seen that the longitudinal section of the sample presents an obvious nanocrystalline structure and the thickness of the film is 1.3 μm.
[0073] Comparative Example 3
[0074] The preparation of an amorphous CuZr-crystalline Cr multilayer film of equal thickness has the same preparation steps as in Example 1, except that the sputtering time of the Cr layer is 9 minutes each time.
[0075] The longitudinal cross-sectional morphology of the amorphous CuZr-crystalline Cr multilayer film of equal thickness obtained in this comparative example is shown in FIG. Fig. 9 As shown by Fig. 9 It can be seen that the longitudinal section of the sample also presents an obvious multilayer film structure, but the thickness of the Cr layer remains unchanged from bottom to top. The nanoindentation test of the multilayer film is carried out, and the results are as follows Figure 2 As shown in Figure 2, the hardness and modulus of the multilayer film by nanoindentation are 10.3 GPa and 168 GPa, respectively. Then, a microcolumn with a diameter of 1 μm and a height of 2 μm was cut in the area of the multilayer film that was not subjected to the nanoindentation test by a focused ion beam. The morphology is shown in Figure 2. Fig.10 The microcolumn is then compressed by nano-indentation technology, and the morphology after compression is shown in Fig.11 As shown by Fig.11 It can be seen that after compression, the microcolumn appears in a bucket shape with obvious cross cracks. The stress-strain curve of the microcolumn compression is shown in Figure 5 As shown, it can be concluded that the yield strength of the multilayer film reaches 2.8 GPa when the strain reaches 50%.
[0076] Comparative Example 4
[0077] An amorphous CuZr-crystalline Al gradient multilayer film is prepared. The preparation steps are the same as those in Example 1, except that the Cr target is replaced by an Al target.
[0078] The longitudinal cross-sectional morphology (SEM image) of the amorphous CuZr-crystalline Al gradient multilayer film obtained in this comparative example is as follows: Fig.12 As shown by Fig.12 It can be seen that the longitudinal section of the sample presents an obvious multilayer film structure, and the thickness of the Al layer increases gradually from bottom to top. From the SEM image, it can also be seen that the interface between the CuZr layer and the Al layer is uneven and there are obvious pores in some areas, indicating that the combination of the two is not as good as CuZr and Cr. The multilayer film was subjected to nanoindentation testing, and the results are as follows Figure 2 As shown in Figure 1, the hardness and modulus of the multilayer film by nanoindentation are 4.2 GPa and 78 GPa respectively. Then, a microcolumn with a diameter of 1 μm and a height of 2 μm (cut from the top layer downwards) is cut in the area of the multilayer film that is not subjected to the nanoindentation test by a focused ion beam, and then the microcolumn is compressed by nanoindentation technology. The stress-strain curve of the microcolumn compression is shown in Figure 1. Figure 5 As shown in Figure 2, it can be concluded that the yield strength of the multilayer film reaches 2.2 GPa when the strain reaches 50%. Fig.13 As shown by Fig.13 It can be seen that obvious large cracks are generated in the upper layers and the Al layer is squeezed and deformed, while the Cr layer in Example 1 does not show obvious squeeze deformation.
[0079] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A tough amorphous CuZr-crystalline Cr gradient multilayer film, characterized in that: It is obtained by alternately stacking amorphous CuZr layers and crystalline Cr layers, wherein the thickness of the amorphous CuZr layers is consistent, and the thickness of the crystalline Cr layers increases gradually from bottom to top; the bottom layer of the tough amorphous CuZr-crystalline Cr gradient multilayer film is the amorphous CuZr layer; The element composition of the amorphous CuZr layer is Cu 50 Zr 50 ; The single layer thickness of the amorphous CuZr layer is 210±5nm; the amorphous CuZr layer has 9 layers in total; There are 8 crystalline Cr layers in total, and the thickness of each layer from bottom to top is 22±5, 44±5, 70±5, 93±5, 124±5, 144±5, 167±5, and 190±5 nm.
2. The method for preparing a tough amorphous CuZr-crystalline Cr gradient multilayer film according to claim 1, characterized in that: The following steps are involved: By using magnetron sputtering technology, using CuZr target material and Cr target material as sputtering raw materials, amorphous CuZr layer and crystalline Cr layer are alternately sputtered and deposited on the substrate to obtain the tough amorphous CuZr-crystalline Cr gradient multilayer film; The sputtering power of the CuZr target is 60W, and the sputtering power of the Cr target is 30W; The sputtering time of each amorphous CuZr layer is 16 min, and the sputtering time of each crystalline Cr layer from bottom to top is 2, 4, 6, 8, 10, 12, 14, and 16 min, respectively.
3. The preparation method according to claim 2, characterized in that: The working pressure of argon gas for the alternate sputtering deposition of the amorphous CuZr layer and the crystalline Cr layer is 1 Pa.
4. The preparation method according to claim 2, characterized in that: Before the alternate sputtering deposition of the amorphous CuZr layer and the crystalline Cr layer, the CuZr target material and the Cr target material are pre-sputtered.
Citation Information
Patent Citations
Preparation method for nanocrystal film with improved plasticity
CN108468032A